Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
Through a two-step coating process and multi-stage sintering technology, the coating layer of the positive electrode material of sodium ion battery is optimized, which solves the problems of insufficient coating thickness, poor conductivity, excessive residual alkali content and serious side reactions, and significantly improves the performance of the material and the life of the battery.
Patent Information
- Application Number
- CN202510130263.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion battery positive electrode material has insufficient thickness, poor conductivity, excessive residual alkali content and serious side reactions, which affect the performance of the material and the life of the battery.
Using a two-step coating process, through high-speed mixing and multi-stage sintering technology, appropriate coating materials and additives are selected, sintering conditions and plasma treatment process are optimized, the quality and conductivity of the coating layer are significantly improved, and the residual alkali content and side reaction risks are reduced.
The quality and uniformity of the coating layer are improved, the conductivity is significantly improved, the residual alkali content is reduced, the side reaction with the electrolyte is reduced, and the performance of the positive electrode material of the sodium ion battery and the life of the battery are significantly improved.
Smart Images

Figure CN119581540A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery materials, and in particular to a sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] As a new type of energy storage device, sodium-ion battery (SIB) has received extensive attention in recent years due to its abundant sodium resources, low cost, and environmental friendliness. Compared with lithium-ion battery (LIB), sodium-ion battery has a wide distribution of sodium resources and abundant reserves, which can effectively alleviate the problem of lithium resource shortage. In addition, the production cost of sodium-ion battery is relatively low, and it has better environmental adaptability and sustainable development potential.
[0003] One of the key components of sodium-ion batteries is the cathode material, whose performance directly affects the capacity, cycle life and rate performance of the battery. At present, common cathode materials for sodium-ion batteries include layered oxides, polyanion compounds and sodium transition metal oxides. Among them, layered oxides have become a hot topic of research due to their high theoretical capacity and good cycle stability.
[0004] In the prior art, there are two methods for preparing layered oxide sodium positive electrode materials. One is to wet-synthesize mixed manganese, iron and nickel salts under appropriate alkaline conditions to directly obtain a hydroxide or carbonate precursor sample, and then mix it evenly with sodium salt and sinter it to obtain a sodium positive electrode material. The other is to directly dry-mix and grind the oxide precursor and the sodium source, and then sinter them to obtain a sodium positive electrode material. Sintering generally adopts a two-time sintering process. The main performance sintering stage is in the first sintering stage, and the coating of the material is mainly in the second sintering stage. Most of the coating methods reported so far have shortcomings, resulting in a high residual alkali content in the positive electrode material, generally more than 10,000, or even more than 20,000, which seriously affects the preparation of the material on the battery core slurry and is prone to jelly. Existing synthetic layered sodium positive electrode materials are prone to problems such as insufficient coating thickness, poor coating conductivity, failure of the coating to reduce the residual alkali in the material to a certain standard such as 5000ppm upon calcination, and high coating activity, which is prone to side reactions with the electrolyte.
[0005] In addition, layered oxides still face other challenges in practical applications, such as poor conductivity, insufficient cycle stability, poor rate performance, etc. Therefore, the development of high-performance cathode materials for sodium-ion batteries has important research value and application prospects. Summary of the invention
[0006] The existing synthetic layered system sodium battery positive electrode materials in the prior art are prone to problems such as insufficient coating thickness, poor coating conductivity, failure of the coating to reduce the residual alkali in the material to a certain standard such as 5000ppm upon calcination, and high coating activity, which is prone to side reactions with the electrolyte. Therefore, the present invention provides a sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery for solving the above problems.
[0007] To achieve the above object, in a first aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery, characterized in that it comprises the following specific steps: S1. providing a sodium source, a sodium ion battery cathode material precursor and an additive, and mixing them at a high speed; S2, sintering the mixed material once, the sintering temperature is 600-1200°C, the sintering time is 8-16h, and a sintered material is obtained; S3, adding a first coating material to the calcined material, mixing the powders at high speed, placing the mixed powders to be left standing at a temperature below -40°C for rapid freezing, removing the solvent by vacuum freeze drying, and leaving the mixture standing for 0.5 to 3 hours, wherein the mass ratio of the first coating material is 0.5 to 5%; S4, adding a second coating material to the powder after standing, mixing the above materials at high speed, and then performing secondary sintering, the sintering temperature is 300-800° C., and the sintering time is 1-8 hours to obtain the desired sodium ion battery positive electrode material; Wherein, the additive is any one of cyanoethyl acrylate, sodium fluoride, sodium phosphate, iron phosphate, sodium borate, and citric acid; the first coating material includes any one or more of polyvinyl alcohol, polyacrylic acid, polyethylene glycol, aminosilane, epoxysilane, cobalt oxalate, and nickel oxalate; the second coating material includes any one or a combination of titanium dioxide, tungsten trioxide, and molybdenum trioxide, and the mass ratio of the second coating material is 0.1~5%.
[0008] In one implementation, in S1, the sodium ion battery positive electrode material precursor has a chemical formula of Ni x Mn y Fe 1-x-y (OH)2, wherein 0.15≤x≤0.35, 0.2≤y≤0.5; the S element content in the sodium ion battery positive electrode material precursor is ≤4000ppm, and the Na / S mass ratio is ≤1.5.
[0009] In one implementation, in S1, the sodium source is industrial sodium carbonate, the added sodium source is 1.01 times the molar amount of the sodium ion battery positive electrode material precursor, and the added mass percentage of the industrial sodium carbonate is 0.5%.
[0010] In one implementation, in S1, S3 and S4, the mixing speed of the high-speed mixing is 400-800 rpm, and the time of the high-speed mixing is 20-60 min.
[0011] In one implementation, during the primary sintering in S2 and the secondary sintering in S4, the temperature is gradually increased or decreased through multi-stage annealing.
[0012] In one implementation, the primary sintering in S2 includes the following specific steps: placing the sample in a sintering furnace, setting the starting temperature to room temperature, heating the temperature to 300-600°C at a heating rate of 3-5°C / min, and keeping the temperature for 0.5-3 hours; continuing to heat the temperature to 900-1200°C at a heating rate of 2-3°C / min, and keeping the temperature for 4-10 hours to obtain the single-fired material.
[0013] In one implementation, after the secondary sintering in S4 is completed, the method further includes: S5, using a low-temperature plasma device to treat the surface of the material after the secondary sintering with ammonia or hydrogen sulfide.
[0014] In one implementation, the processing step of S5 specifically includes: S51, cooling the sintered material to room temperature, taking it out and crushing it into particles of 10-50 μm; S52, evenly distributing the samples on a sample tray in the plasma processing chamber; S53, reducing the pressure in the chamber to 10-100 Pa, and introducing nitrogen at a rate of 10-50 mL / min; S54, start the RF power supply, set the frequency to 13.56 MHz, control the power within the range of 50-200 W, activate the plasma, the processing time is 5-30 minutes, and take it out after cooling.
[0015] In a second aspect, the present invention further provides a sodium ion battery positive electrode material, which is prepared by the above-mentioned method for preparing the sodium ion battery positive electrode material.
[0016] In a second aspect, the present invention further provides a sodium ion battery, which uses the above-mentioned sodium ion battery positive electrode material.
[0017] Beneficial effects: In the present invention, the quality and uniformity of the coating layer are improved through a two-step coating process; the conductivity of the coating layer is significantly improved through the selection of coating materials and process optimization; the residual alkali content is effectively reduced through multi-stage sintering and optimized design of the coating layer to meet higher material purity requirements; the reduction of the chemical activity of the coating layer is solved through material selection and surface passivation process, which effectively reduces the side reaction with the electrolyte, and effectively addresses the problems of insufficient coating thickness, poor conductivity, excessive residual alkali content and serious side reactions in the process of synthesizing layered system sodium ion battery positive electrode materials, thereby providing a better method for preparing sodium ion battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The present invention provides a flow chart of the steps of preparing the positive electrode material for a sodium ion battery.
[0019] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0021] The present invention provides a method for preparing a positive electrode material for a sodium ion battery, characterized in that it comprises the following specific steps: S1. providing a sodium source, a sodium ion battery cathode material precursor and an additive, and mixing them at a high speed; S2, sintering the mixed material once, the sintering temperature is 600-1200°C, the sintering time is 8-16h, and a sintered material is obtained; S3, adding a first coating material to the calcined material, mixing the powders at high speed, placing the mixed powders to be left standing at a temperature below -40°C for rapid freezing, removing the solvent by vacuum freeze drying, and leaving the mixture standing for 0.5 to 3 hours, wherein the mass ratio of the first coating material is 0.5 to 5%; S4, adding a second coating material to the powder after standing, mixing the above materials at high speed, and then performing secondary sintering, the sintering temperature is 300-800° C., and the sintering time is 1-8 hours to obtain the desired sodium ion battery positive electrode material; The additive is any one of cyanoethyl acrylate, sodium fluoride, sodium phosphate, iron phosphate, sodium borate, and citric acid; the first coating material includes any one or more of polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyethylene glycol (PEG), KH-550 (aminosilane), KH-560 (epoxysilane), cobalt oxalate, and nickel oxalate; the second coating material includes any one or a combination of titanium dioxide, tungsten trioxide, and molybdenum trioxide, and the mass ratio of the second coating material is 0.1~5%.
[0022] Specifically, cyanoethyl acrylate is used to improve the adhesion of electrode materials and enhance the bonding force between particles, thereby improving the mechanical strength and electrochemical properties of the electrode. Sodium fluoride is used to improve the thermal stability and electrochemical stability of the material, prevent the material from decomposing at high temperatures, and improve the cycle performance of the battery. Sodium phosphate and iron phosphate are used to provide additional phosphorus sources, promote the formation of the crystal structure of the positive electrode material, and enhance the conductivity and electrochemical activity of the material. Sodium borate is used to improve the corrosion resistance of the material and prevent the electrode material from being corroded by the electrolyte during the operation of the battery. Citric acid is used as a chelating agent to help evenly disperse metal ions, promote uniform mixing of precursor substances, and improve the uniformity and electrochemical properties of the material.
[0023] Specifically, in the first coating material, polyvinyl alcohol, polyacrylic acid and polyethylene glycol can form a protective film to prevent direct contact between positive electrode material particles, reduce side reactions between particles, and improve the material's cycle performance and stability. Aminosilane and epoxysilane can improve the material's surface properties, enhance the material's stability in the electrolyte, and improve the battery's long cycle life through the action of silane coupling agents. Cobalt oxalate and nickel oxalate enhance the material's conductivity and electrochemical stability by forming a metal oxide coating layer on the material's surface, preventing the material from undergoing structural changes during the electrochemical cycle.
[0024] Specifically, in the second coating material, titanium dioxide has good electrochemical stability and conductivity, and can form a dense protective layer on the surface of the material to prevent the electrode material from being corroded by the electrolyte during the charge and discharge process, thereby improving the cycle performance of the material. Tungsten trioxide and molybdenum trioxide have high conductivity and high electrochemical activity, which can improve the conductivity and electrochemical reaction rate of the material, and enhance the rate performance and electrochemical stability of the electrode.
[0025] By adding these additives, the first coating material and the second coating material, the mechanical strength and electrochemical stability of the material can be significantly improved, the uniform distribution of the material and the formation of the crystal structure can be promoted, the conductivity and electrochemical reaction rate of the material can be enhanced, the corrosion resistance and thermal stability of the material can be improved, and the cycle life and rate performance of the battery can be improved.
[0026] Specifically, in S1, the sodium ion battery positive electrode material precursor has a chemical formula of Ni x Mn y Fe 1-x-y (OH)2, wherein 0.15≤x≤0.35, 0.2≤y≤0.5; the S content in the sodium ion battery positive electrode material precursor is ≤4000ppm, and the Na / S mass ratio is ≤1.5. The sodium source is industrial sodium carbonate, and the added sodium source is 1.01 times the molar amount of the sodium ion battery positive electrode material precursor.
[0027] In S1, S3 and S4, the mixing speed of high-speed mixing is 400-800 rpm, and the time of high-speed mixing is 20-60 min. By mixing the sodium source, sodium ion battery cathode material precursor and additives at high speed, the full mixing of the components is ensured, and the uniformity and efficiency of the reaction are improved. The speed and time of high-speed mixing optimize the uniform dispersion of the powder, which is conducive to the uniform reaction in the subsequent sintering process.
[0028] During the primary sintering in S2 and the secondary sintering in S4, the temperature is gradually increased or decreased through multi-stage annealing. Specifically, the sample is placed in a sintering furnace, the starting temperature is set to room temperature, and the temperature is increased to 300-600°C at a heating rate of 3-5°C / min, and kept warm for 0.5-3 hours; the temperature is continued to be increased to 900-1200°C at a heating rate of 2-3°C / min, and kept warm for 4-10 hours to obtain the first-fired material. Correspondingly, when it is cooled down, the intermediate annealing stage is performed: the intermediate annealing is performed after cooling to 600-800°C, and the temperature is kept warm for 1-4 hours. This stage helps to release thermal stress and reduce crystal defects and microcracks of the material. Slowly cool to 300-400°C and keep for 1-3 hours to further optimize the particle surface. Finally, cool to room temperature at a rate of 1-3°C / min to avoid microstructural damage caused by rapid cooling. By gradually raising or lowering the temperature through multi-stage annealing, the grain growth and phase transition of the material can be effectively controlled to obtain an ideal material microstructure.
[0029] After the secondary sintering in S4 is completed, the method further includes: S5, using a low temperature plasma device to treat the surface of the secondary sintered material with ammonia or hydrogen sulfide. Further, the processing steps in S5 specifically include: S51, cooling the sintered material to room temperature, taking it out and crushing it into particles of 10-50 μm; S52, evenly distributing the samples on a sample tray in the plasma processing chamber; S53, reducing the pressure in the chamber to 10-100 Pa, and introducing nitrogen at a rate of 10-50 mL / min; S54, start the RF power supply, set the frequency to 13.56 MHz, control the power within the range of 50-200 W, activate the plasma, the processing time is 5-30 minutes, and take it out after cooling.
[0030] In S5, the surface of the cathode material can be further modified by low-temperature plasma equipment and ammonia or hydrogen sulfide treatment to improve the electrochemical activity and conductivity of the material. During the plasma treatment process, plasma activation can introduce nitrogen or sulfur functional groups, improve the surface chemical properties of the material, and enhance its electrochemical performance.
[0031] The present invention also provides a plurality of embodiments and comparative examples to further explain the technical solution provided by the present invention.
[0032] Embodiment 1, Materials preparation: Sodium source: industrial sodium carbonate; Sodium ion battery cathode material precursor: Ni 0.2 Mn 0.3 Fe 0.5 (OH)2; Additive: cyanoethyl acrylate; First coating material: polyvinyl alcohol (PVA); Second coating material: titanium dioxide; Specific preparation steps of sodium ion battery positive electrode materials: S1: Industrial sodium carbonate (1.01 times the molar amount of sodium ion battery cathode material precursor) and Ni 0.2 Mn 0.3 Fe 0.5 The (OH)2 precursor and cyanoethyl acrylate (mass fraction 0.5%) were mixed at a high speed of 600 rpm for 30 minutes.
[0033] S2: The mixed material is sintered at 800° C. for 10 hours to obtain a sintered material.
[0034] S3: Add 3% by mass of PVA to the calcined material, mix at high speed, freeze the powder quickly below -40°C, remove the solvent by vacuum freeze drying, and let it stand for 1 hour.
[0035] S4: Add 2% by mass of titanium dioxide to the powder after standing, mix at high speed, and sinter at 500°C for 5 hours to obtain a positive electrode material for a sodium ion battery.
[0036] S5: Use low-temperature plasma equipment to treat the surface of the secondary sintered material with ammonia for 15 minutes to obtain the required sodium ion battery positive electrode material.
[0037] Screening, iron removal and packaging: The prepared material is passed through a 200-mesh sieve, and then iron is removed using a 12000gs electromagnetic iron remover. After iron removal, vacuum packaging is performed.
[0038] Button battery production: Sodium battery material button battery assembly uses 2032 button battery, the electrolyte conductive material is 1M sodium hexafluorophosphate, the diaphragm is special glass fiber, the negative electrode is sodium sheet, the packaging material is domestic spring pattern, the positive electrode material is the sodium ion battery positive electrode material in the above embodiment 1, the test voltage range is 2.0-4.1V, and the Blue Electric button battery tester is used to collect capacity and other data.
[0039] The test result data are shown in Table 1.
[0040] Embodiment 2, Materials preparation: Sodium source: industrial sodium carbonate; Precursor chemical formula: Ni 0.25 Mn 0.25 Fe 0.5 (OH)2; Additives: iron phosphate; First coating material: cobalt oxalate; Second coating material: tungsten trioxide; Specific preparation steps of sodium ion battery positive electrode materials: S1: Industrial sodium carbonate (1.01 times the molar amount of sodium ion battery cathode material precursor) and Ni 0.25 Mn 0.25 Fe 0.5 The (OH)2 precursor and iron phosphate (mass fraction 0.5%) were mixed at a high speed of 600 rpm for 30 minutes.
[0041] S2: The mixed material is sintered at 900° C. for 12 hours to obtain a sintered material.
[0042] S3: Add 4% by mass of cobalt oxalate to the calcined material, mix at high speed, freeze the powder quickly below -40°C, remove the solvent by vacuum freeze drying, and let it stand for 1 hour.
[0043] S4: Add 5% by mass of tungsten trioxide to the powder after standing, mix at high speed, and sinter at 600°C for 6 hours to obtain a positive electrode material for a sodium ion battery.
[0044] S5: Using low-temperature plasma equipment, the surface of the secondary sintered material is treated with hydrogen sulfide for 20 minutes to obtain the desired sodium ion battery positive electrode material.
[0045] The other steps are the same as those in Example 1 and will not be described in detail here. The test result data are shown in Table 1.
[0046] Embodiment 3, Materials preparation: Sodium source: industrial sodium carbonate; Precursor chemical formula: Ni 0.3 Mn 0.2 Fe 0.5 (OH)2; Additives: sodium fluoride; First coating material: polyethylene glycol; Second coating material: molybdenum trioxide; Specific preparation steps of sodium ion battery positive electrode materials: S1: Industrial sodium carbonate (1.01 times the molar amount of sodium ion battery cathode material precursor) and Ni 0.25 Mn 0.25 Fe 0.5 The (OH)2 precursor and sodium fluoride (mass fraction 0.5%) were mixed at a high speed of 600 rpm for 30 minutes.
[0047] S2: The mixed material is sintered at 850° C. for 11 hours to obtain a sintered material.
[0048] S3: Add 1% by mass of polyethylene glycol to the calcined material, mix at high speed, freeze the powder quickly below -40°C, remove the solvent by vacuum freeze drying, and let it stand for 1 hour.
[0049] S4: 1.5% by mass of molybdenum trioxide was added to the powder after standing, mixed at high speed, and sintered at 550°C for 4 hours to obtain a positive electrode material for a sodium ion battery.
[0050] S5: Use low-temperature plasma equipment to treat the surface of the secondary sintered material with ammonia for 10 minutes to obtain the required sodium ion battery positive electrode material.
[0051] The other steps are the same as those in Example 1 and will not be described in detail here. The test result data are shown in Table 1.
[0052] Embodiment 4, Materials preparation: Sodium source: industrial sodium carbonate; Precursor chemical formula: Ni 0.15 Mn 0.35 Fe 0.5 (OH)2; Additives: sodium phosphate; First coating material: aminosilane; Second coating material: titanium dioxide; Specific preparation steps of sodium ion battery positive electrode materials: S1: Industrial sodium carbonate (1.01 times the molar amount of sodium ion battery cathode material precursor) and Ni 0.15 Mn 0.35 Fe 0.5 The (OH)2 precursor and sodium phosphate (mass fraction 0.5%) were mixed at a high speed of 600 rpm for 30 minutes.
[0053] S2: The mixed material is sintered at 950° C. for 14 hours to obtain a sintered material.
[0054] S3: Add 2.5% by mass of aminosilane to the calcined material, mix at high speed, and then freeze the powder quickly below -40°C. Remove the solvent by vacuum freeze drying and let it stand for 1 hour.
[0055] S4: Add 2.5% by mass of titanium dioxide to the powder after standing, mix at high speed, and sinter at 650°C for 7 hours to obtain a positive electrode material for a sodium ion battery.
[0056] S5: Using low-temperature plasma equipment, the surface of the secondary sintered material is treated with hydrogen sulfide for 25 minutes to obtain the desired sodium ion battery positive electrode material.
[0057] The other steps are the same as those in Example 1 and will not be described in detail here. The test result data are shown in Table 1.
[0058] Comparative Example 1 Materials preparation: Sodium source: industrial sodium carbonate; Precursor chemical formula: Ni 0.2 Mn 0.3 Fe 0.5 (OH)2; Additives: None; Covering material: None; Plasma treatment: No; The other steps are the same as those in Example 1 and will not be described in detail here. The test result data are shown in Table 1.
[0059] Comparative Example 2 Materials preparation: Sodium source: industrial sodium carbonate; Precursor chemical formula: Ni 0.2 Mn 0.3 Fe 0.5 (OH)2; Additive: cyanoethyl acrylate; Covering material: None; Plasma treatment: No; The other steps are the same as those in Example 1 and will not be described in detail here. The test result data are shown in Table 1.
[0060] Comparative Example 3 Materials preparation: Materials preparation: Sodium source: industrial sodium carbonate; Precursor chemical formula: Ni 0.2 Mn 0.3 Fe 0.5 (OH)2; Additives: None; Covering material: None; Plasma treatment: The surface of the secondary sintered material is treated with ammonia for 15 minutes; The other steps are the same as those in Example 1 and will not be described in detail here. The test result data are shown in Table 1.
[0061] Table 1. Test results of various embodiments and comparative examples Through the above examples and comparisons and the results of Table 1, it can be seen that different coating materials and plasma treatments have a significant effect on the performance of the positive electrode materials of sodium ion batteries. At the same time, the high residual alkali data in the comparative example show that the materials lacking coating and plasma treatment are poor in residual alkali control, which leads to poor battery performance and life. The coating and plasma treatment processes are significantly effective in reducing the residual alkali, which is very important for improving the overall performance of sodium ion batteries.
[0062] In summary, in the present invention, the quality and uniformity of the coating layer are improved through a two-step coating process; the conductivity of the coating layer is significantly improved through the selection of coating materials and process optimization; the residual alkali content is effectively reduced through multi-stage sintering and optimized design of the coating layer to meet higher material purity requirements; the reduction of the chemical activity of the coating layer is solved through material selection and surface passivation process, which effectively reduces the side reaction with the electrolyte, and effectively addresses the problems of insufficient coating thickness, poor conductivity, excessive residual alkali content and serious side reactions in the process of synthesizing layered system sodium ion battery positive electrode materials, thereby providing a better method for preparing sodium ion battery positive electrode materials.
[0063] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The specific steps include: S1. providing a sodium source, a sodium ion battery cathode material precursor and an additive, and mixing them at a high speed; S2, sintering the mixed material once, the sintering temperature is 600-1200°C, the sintering time is 8-16h, and a sintered material is obtained; S3, adding a first coating material to the calcined material, mixing the powders at high speed, placing the mixed powders to be left standing at a temperature below -40°C for rapid freezing, removing the solvent by vacuum freeze drying, and leaving the mixture standing for 0.5 to 3 hours, wherein the mass ratio of the first coating material is 0.5 to 5%; S4, adding a second coating material to the powder after standing, mixing the above materials at high speed, and then performing secondary sintering, the sintering temperature is 300-800° C., and the sintering time is 1-8 hours to obtain the desired sodium ion battery positive electrode material; Wherein, the additive is any one of cyanoethyl acrylate, sodium fluoride, sodium phosphate, iron phosphate, sodium borate, and citric acid; the first coating material includes any one or more of polyvinyl alcohol, polyacrylic acid, polyethylene glycol, aminosilane, epoxysilane, cobalt oxalate, and nickel oxalate; the second coating material includes any one or a combination of titanium dioxide, tungsten trioxide, and molybdenum trioxide, and the mass ratio of the second coating material is 0.1~5%.
2. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: In S1, the sodium ion battery cathode material precursor has a chemical formula of Ni x Mn y Fe 1-x-y (OH)2, wherein 0.15≤x≤0.35, 0.2≤y≤0.5; the S element content in the sodium ion battery positive electrode material precursor is ≤4000ppm, and the Na / S mass ratio is ≤1.
5.
3. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: In S1, the sodium source is industrial sodium carbonate, the added sodium source is 1.01 times the molar amount of the sodium ion battery positive electrode material precursor, and the added mass percentage of the industrial sodium carbonate is 0.5%.
4. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: In S1, S3 and S4, the mixing speed of the high-speed mixing is 400-800 rpm, and the time of the high-speed mixing is 20-60 min.
5. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: During the primary sintering in S2 and the secondary sintering in S4, the temperature is gradually increased or decreased through multi-stage annealing.
6. The method for preparing a positive electrode material for a sodium ion battery according to claim 5, characterized in that: The primary sintering in S2 includes the following specific steps: placing the sample in a sintering furnace, setting the starting temperature to room temperature, heating the temperature to 300-600°C at a heating rate of 3-5°C / min, and keeping the temperature for 0.5-3 hours; continuing to heat the temperature to 900-1200°C at a heating rate of 2-3°C / min, and keeping the temperature for 4-10 hours to obtain the once-fired material.
7. The method for preparing a positive electrode material for a sodium ion battery according to claim 1, characterized in that: After the secondary sintering in S4 is completed, the method further includes: S5, using low temperature plasma equipment to treat the surface of the material after the secondary sintering by ammonia or hydrogen sulfide.
8. The method for preparing a positive electrode material for a sodium ion battery according to claim 7, characterized in that: The processing steps of S5 specifically include: S51, cooling the sintered material to room temperature, taking it out and crushing it into particles of 10-50 μm; S52, evenly distributing the samples on a sample tray in the plasma processing chamber; S53, reducing the pressure in the chamber to 10-100 Pa, and introducing nitrogen at a rate of 10-50 mL / min; S54, start the RF power supply, set the frequency to 13.56 MHz, control the power within the range of 50-200 W, activate the plasma, the processing time is 5-30 minutes, and take it out after cooling.
9. A sodium ion battery positive electrode material, characterized in that: The cathode material is prepared by the method for preparing the sodium ion battery cathode material according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery positive electrode material according to claim 9 is used.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material and preparation method thereof
CN116207232A
Nickel-iron-manganese layered oxide as well as preparation method and application thereof
CN116282222A
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN117466346A
High-stability sulfate sodium ion battery positive electrode material and preparation method thereof
CN118712367A
Sodium-ion battery layered positive electrode material with low residual alkali content and preparation method of sodium-ion battery layered positive electrode material
CN118919710A
Cited By
Method for regenerating waste polycrystalline ternary lithium positive electrode into single crystal ternary lithium positive electrode
CN121601852A